Corpo e palavra: ouvir, ver e sentir o poema no Ensino Fundamental II - Laura Alves Moreira (2020)
The basic school has often not been an environment that favors or values students' contact with literature (and the arts in general). However, great literature clearly can play a very important role forming students that will be more aware of the problems and achievements of their time, individuals more sensitive to our world, which is not just a tangle of ideas and concepts, but also a world full of objects and other individuals to be perceived. What has constantly been seen in the school environment is the students' lack of contact with literature, its particularities in terms of structuring and what it is capable of providing. And it is not difficult to perceive the negative effects of this. Therefore, this project proposes organized workshops to guide the students to make a direct observation of different aspects of texts of the genre poem in order to arouse their interest in this genre, based on the perception of the particularities of the texts and from the aesthetic enjoyment that they can take from those texts. The specific purpose of these activities would be to get students to realize the existence (and their mechanisms of constitution) of different levels or strata of meaning, specifically the layers named by Ezra Pound of "melopeia" and "fanopeia". Therefore, the project is based on a bibliographical research through which a pedagogical intervention was constituted whose objective is for students to arrive at some knowledge about the peculiarities of the poem genre less on the path of reflection and more by attentive observation and direct experience with the texts.